Systematic Review on Public Services in the Implementation of Smart City Using VOSviewer - Darmawan, Bagas Rahmat; Ramadhan, Muhammad Raihan; Nurmandi, Achmad; Fridayani, Helen Dian; Loilatu, Mohammad Jafar (ARISTO, 2025)
This research focuses on the development of online services using Artificial Intelligence (AI) created to build a concept of smart city based on E-Government. The focus of this research is to answer the question: Is the implementation of smart city effective in improving the quality of public services? The impact of smart city implementation on the development of public services is also discussed. The results of this research show that governments in the Asian region are increasingly utilizing AI for ubiquitous connectivity, and a range of other technologies to help solve the most pressing urban issues, ranging from population growth and congestion to environmental sustainability as well as improving administrative effectiveness. The use of chatbots is also utilized by the governments in Asia to assist conversations with AI technologies in managing service issues. These findings shed light on an important theoretical foundation focused on human-computer interaction and clarify the benefits of using AI technologies.